Efficacy of combined use of Suvorexant and Ramelteon in preventing postoperative delirium: a retrospective comparative study - Shoya Ikeuchi; Rei Tanaka; Teiichi Sugiura; Kaori Shinsato; Akane Wakabayashi; Junya Sato; Keiko Suzuki; Michihiro Shino (BMC, 2023)
Abstract Background Suvorexant and ramelteon have been presented as useful for preventing postoperative delirium. Previous studies reported on the comparison with benzodiazepine hypnotics which have been known for the risk for inducing delirium, but the comparison with patients not taking any hypnotics has not been reported yet. Therefore, we assessed the incidence rates for postoperative delirium comparing cancer patients who received preoperative combined administration with suvorexant and ramelteon and those not taking any hypnotics. Methods Among 110 cancer patients who underwent surgeries at the Division of Hepato-Biliary-Pancreatic Surgery at the Shizuoka Cancer Center between April 1, 2017 and June 30, 2020, 50 patients who received combined administration with suvorexant and ramelteon from 7 days prior to their surgeries and 60 patients who did not take any hypnotics including suvorexant and ramelteon were classified. They were retrospectively observed during the 7 days from their surgeries onward to compare the cumulative incidence rates for postoperative delirium. Results The cumulative incidence rate for postoperative delirium during the 7 days in the combined-administration group was 14.0% (7/50), while that for the no-hypnotic group was 36.7% (22/60), which proved that the incidence rate for the former was significantly low (OR: 0.28, 95%CI: 0.11-0.73, P = 0.009). Conclusions The present study suggests that the preventive combined administration with suvorexant and ramelteon starting from the preoperative period for cancer patients can be effective in lowering the incidence rate for postoperative delirium. Trial registration Retrospectively registered.